Effect of Al2O3 particles on mechanical and tribological properties of Al–Mg dual-matrix nanocomposites. Issue 5 (1st April 2020) - Eltaher, M.A.; A.Wagih,; Melaibari, A.; Fathy, A.; Lubineau, G.
Abstract: This article aims to manufacture homogenous dual-matrix Al–Mg/Al2 O3 nanocomposite from their raw materials and give insight into the correlation between powder morphology, crystallite structure and their mechanical and tribological properties. Al–Mg dual-matrix reinforced with micro/nano Al2 O3 particles was manufactured by a novel double high-energy ball milling process followed by a cold consolidation and sintering. Microstructure and phase composition of the prepared samples were characterized using FE-SEM, EDS and XRD inspections. Mechanical and wear properties were characterized using compression and sliding wear tests. The results showed that a milling of Mg with Al2 O3 particles in an initial step before mixing with Al has the beneficial of well dispersion of Al2 O3 nanoparticles in Al–Mg dual matrix. The Al–Mg dual matrix reinforced with nano-size Al2 O3 showed 3.29-times smaller crystallite size than pure Al. Moreover, the hardness and compressive strength are enhanced by adding nano-size Al2 O3 with Al–Mg dual matrix composite while the ductility is maintained relatively high. Additionally, the wear rate of this composite was reduced by a factor of 2.7 compared to pure Al. The reduced crystallite size, the dispersion of Al2 O3 nanoparticles and the formation of (Al–Mg)ss were the main improvement factors for mechanical and wear properties.